KEABSAHAN KONTRAK DALAM EKONOMI SYARIAH: PERSPEKTIF FIQH MUAMALAH - Faiq Fatih Alwan; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The validity of contracts in Islamic economics is one of the fundamental aspects in fiqh muamalah which functions to ensure that transactions run in accordance with Islamic principles. This study discusses the requirements for valid contracts in Islamic economics based on the provisions of fiqh muamalah, including the pillars and conditions of the contract, prohibitions in transactions (riba, gharar, and maysir), and the relevance of Islamic contract law in the modern economic system. This study also compares Islamic contracts with conventional contract law to identify the advantages and challenges in their implementation, especially in Islamic banking and business in Indonesia. With a descriptive-analytical approach, this article highlights the importance of compliance with Islamic principles in order to create a fair and just economic system.